Mobile Instant Messaging and Its Potential to Reduce Anxiety in English as a Foreign Language Speaking Class - Rachman, Dzul; ., Sunarti (International Journal of Engineering and Technology, 2019)
This study examines of students’ speaking anxiety, self-efficacy, speaking achievement and their feeling about the activities conducted using WhatsApp activities in English as a Foreign Language speaking class. Three instruments used to collect the data in this study were the questionnaire, speaking test and interview. The data were analyzed by using descriptive statistic to find out the level of students speaking anxiety and self-efficacy. The multiple regressions were to investigate the relationship between variables and two-way ANOVA to know the significant differences between the variables and interview to get information about mobile application activities through focus group discussion. The integration of Smartphone in teaching and learning English can effectively reduce the students’ speaking anxiety, and makes a good score in speaking English as a Foreign Language. Furthermore, the researcher finds that foreign language speaking anxiety was statistically predicted students’ speaking achievement. The decreasing in speaking anxiety means the increase in students’ speaking achievement. Finally, students indicated if they are eager to continue using WhatsApp for enhancing their speaking abilities as a part of classroom activities for the future.